2010
DOI: 10.1111/j.1582-4934.2009.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

The anti‐angiogenic factor PEDF is present in the human heart and is regulated by anoxia in cardiac myocytes and fibroblasts

Abstract: Cardiac diseases such as myocardial infarction and heart failure are among the leading causes of death in western societies. Therapeutic angiogenesis has been suggested as a concept to combat these diseases. The biology of angiogenic factors expressed in the heart such as vascular endothelial growth factor (VEGF) is well studied, whereas data on anti-angiogenic mediators in the heart are scarce. Here we study the expression of the anti-angiogenic factor pigment epithelium-derived factor (PEDF) in the human hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 21 publications
4
32
0
Order By: Relevance
“…While much research has focused on evaluating the therapeutic potential of PEDF against a myriad of tumors (5), cardiovascular diseases (48,49), and other pathologies (10,11), little is known about the physiological function of PEDF. We present the first evidence of the important role for PEDF in the regulation of angiogenesis and ECM remodeling during dermal wound repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While much research has focused on evaluating the therapeutic potential of PEDF against a myriad of tumors (5), cardiovascular diseases (48,49), and other pathologies (10,11), little is known about the physiological function of PEDF. We present the first evidence of the important role for PEDF in the regulation of angiogenesis and ECM remodeling during dermal wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…While various tumors (58) and ischemic hearts (49) express relatively low levels of PEDF, a recent study showed that high systemic levels of PEDF may be etiologic for impaired healing in diabetics due to excessive antiangiogenesis (45). PEDF is produced by quiescent FBs (15,44) in normoxic conditions (49) and by keratinocytes (KCs) (14), and it is readily secreted into the ECM. Analyses of its amino acid sequence (34) and its crystal structure (54) have revealed distinct binding sites for ECM components collagen-1 (35,39) and glycosaminoglycans (3), including heparin (59,66) and hyaluronan (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15] Although first isolated from fetal human retinal pigment (choroid) epithelial cells, like many other NTF, PEDF is expressed in a wide variety of tissues including brain, spinal cord, skeletal muscle, heart, endothelial cells, and osteoblasts. [16][17][18][19][20] PEDF has an array of unique properties including neuroprotective, anti-angiogenic, antiinflammatory, anti-oxidative, and antitumorigenic activities. [21][22][23][24][25][26][27] PEDF is a multifaceted NTF that is active in a variety of ocular disorders including diabetic retinopathy and ischemic degeneration.…”
mentioning
confidence: 99%
“…2 It is ubiquitous in humans and is functionally involved in biological processes such as antiangiogenesis, endothelial cell migration and inhibition of differentiation of tumour and neural cells. [3][4][5][6] There are few studies regarding PEDF expression in the skin, 7,8 and none in condyloma acuminatum. The aim of the present study, therefore, was to investigate SERPINF1 mRNA and PEGF protein levels in condyloma acuminatum and in healthy skin, using reverse transcription-polymerase chain reaction (RT-PCR) and Western blotting, respectively.…”
Section: Introductionmentioning
confidence: 99%